2004
DOI: 10.1016/j.cardiores.2003.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of neutrophils in the pathogenesis of lethal myocardial reperfusion injury

Abstract: Neutrophils respond to myocardial ischemia-reperfusion in a manner similar to the bacterial invasion of a host. The inflammatory-like response that follows the onset of reperfusion involves intense interactions with the coronary vascular endothelium, arterial wall, and cardiomyocytes in a very well-choreographed manner. Neutrophils have been implicated as primary and secondary mediators of lethal injury after reperfusion to coronary vascular endothelium and cardiomyocytes. The involvement of neutrophils in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
429
0
16

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 593 publications
(457 citation statements)
references
References 201 publications
(157 reference statements)
12
429
0
16
Order By: Relevance
“…Third, we show that MSC‐mediated adenosine prevents significant increases in ROS formation following injury. While this effect is likely attributable to reduction of ROS formation from several cell sources (ie, myocytes and fibroblasts), neutrophils are a known significant source of H 2 O 2 and superoxide in vivo 53. Finally, we show that MSCs require CD73‐mediated adenosine production to improve cardiac function following MI/R injury.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Third, we show that MSC‐mediated adenosine prevents significant increases in ROS formation following injury. While this effect is likely attributable to reduction of ROS formation from several cell sources (ie, myocytes and fibroblasts), neutrophils are a known significant source of H 2 O 2 and superoxide in vivo 53. Finally, we show that MSCs require CD73‐mediated adenosine production to improve cardiac function following MI/R injury.…”
Section: Discussionmentioning
confidence: 70%
“…By day 3, however, cell necrosis decreases substantially and may deprive MSCs of the extracellular AMP substrate necessary to continue generating adenosine. Despite this time‐limited effect, adenosine appears to be a potent signaling molecule within the first 24 hours of injury, which serves to blunt the rapid and robust infiltration of circulating leukocytes, a process that has been well documented to propagate myocardial necrosis 2, 53. While the duration of effect for APCP on MSCs after in vivo implantation is not completely clear, Figure 3 would suggest it is temporary since innate immune cell infiltration is significantly reduced at day 1 but not at day 3, by eMSC‐treated animals compared with those treated with APCP‐eMSCs post‐MI/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…However, these cells were not identifiable as apoptotic. The Evans blue stained cardiomyocytes may have received a lethal mechanical injury at the time of exposure, although briefly delayed injury may have occurred from communication via gap junctions (GarciaDorado et al 2004), or by the activity of the infiltrating inflammatory cells (Vinten-Johansen, 2004), which are processes implicated in cardiomyocyte injury. The Evans blue staining indicated permeabilization of the cardiomyocyte plasma membrane, which apparently led to gradual degeneration, necrosis and removal by the normal inflammatory and phagocytic healing process after about 1-2 d. A photomicrograph of a section of a heart sample 4 hr after MCE and stained using the ApopTag® system, which shows TUNEL positive cardiomyocyte nuclei (A).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro experiments suggested that the mechanism of neutrophil-cardiomyocyte adhesion is dependent on CD18 integrin activation on neutrophils and on expression of ICAM-1, one of the primary ligands for the CD18 integrins [208], by injured cardiomyocytes. However, the in vivo significance of neutrophil-induced cardiomyocyte injury remains unknown [209]. Neutrophil depletion in animals undergoing reperfused myocardial infarction led to a marked decrease in infarct size [210,211] suggesting that a significant amount of myocardial injury induced by coronary artery occlusion followed by reperfusion may be neutrophil-dependent [212].…”
Section: The Concept Of Neutrophil-mediated Cardiomyocyte Injurymentioning
confidence: 99%